Effect of α-Tocopherol, Storage Temperature and Storage Time on Quality Characteristics and Oxidative Stability of Chicken Kavurma, traditional Turkish cooked meat product - Nacak, B; Dikici, A; Yel, N; Zaimoğulları, K; İpek, G; Özer, M (Journal of the Hellenic Veterinary Medical Society, 2023)
During storage of meat products, 4°C storage temperature is recommended however temperature in retails could rise to 15°C and maintaining quality of products becomes a challenge at higher temperatures. Thus, the aim of present study was determining the effects of antioxidant usage and storage temperature on some quality characteristics and lipid oxidation stability of chicken kavurma during 4-month storage at 4°C and 10°C. For this purpose, two different kavurma sample (C: without antioxidant, A:with 300 ppm α-tocopherol) were stored at 4°C and 10°C. Chemical composition, salt, texture profile analysis, color and lipid oxidation (peroxide values and TBARS values) of samples were monitored. Using α-tocopherol in formulation did not affect the chemical composition and texture of samples, all parameters were found within standards. Storage time has significant influence on pH, color and lipid oxidation of samples. Using α-tocopherol and higher storage temperature resulted higher peroxide values. During 4-month storage, lipid oxidation results significantly increased, the lowest TBARS value was found in 4A sample. Storage temperature affected only a* values while antioxidant usage affected only b* values of samples. As a result, using 300 ppm α-tocopherol can help maintaining quality and oxidative stability of chicken kavurma sold in retails.